2022
DOI: 10.1007/s00024-022-03028-6
|View full text |Cite|
|
Sign up to set email alerts
|

Climatology of Medium-Scale Traveling Ionospheric Disturbances (MSTIDs) Observed with GPS Networks in the North African Region

Abstract: We present for the first time the climatology of medium-scale traveling ionospheric disturbances (MSTIDs) by using Global Positioning System (GPS) receiver networks on geomagnetically quiet days (Kp ≤ 3) over the North African region during 2008–2016. The ionospheric Total Electron Content (TEC) were estimated from the dual-frequency GPS measurements, and the TEC perturbations (dTEC) data were derived from the estimated TEC data. We focused on the TEC perturbations (dTEC) associated MSTIDs and statistically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…This threshold value of the TIDs events was established by analyzing the standard deviation of all wave-like patterns identified in the MNIG station. Other authors have used threshold values between 0.07 -1 TECu [9,13,18], which agree with the value used in this work. It is important to mention that the amplitude was calculated using the mean value approximation between the upper and lower points of the disturbance, referred to as the average absolute amplitude.…”
Section: Estimation Of Detrended Tec (Dtec) and Identification Of Tid...supporting
confidence: 82%
“…This threshold value of the TIDs events was established by analyzing the standard deviation of all wave-like patterns identified in the MNIG station. Other authors have used threshold values between 0.07 -1 TECu [9,13,18], which agree with the value used in this work. It is important to mention that the amplitude was calculated using the mean value approximation between the upper and lower points of the disturbance, referred to as the average absolute amplitude.…”
Section: Estimation Of Detrended Tec (Dtec) and Identification Of Tid...supporting
confidence: 82%
“…Moreover, Oluwadare et al. (2022) pointed out that the MSTIDs can be potentially generated by the primary waves which survive the dissipation or can possibly be caused by secondary GWs or even both these waves can possibly propagate further up to the thermosphere. These authors also pointed out that lower atmospheric GWs with convective sources penetrate into the thermosphere as higher order GWs.…”
Section: Discussionmentioning
confidence: 99%
“…Vadas & Azeem (2021) suggested that during the convective processes, local body forces act onto the atmosphere which accelerates the neutral wind in the primary direction of GWs and sometimes also leads to the generation of secondary waves. Moreover, Oluwadare et al (2022) pointed out that the MSTIDs can be potentially generated by the primary waves which survive the dissipation or can possibly be caused by secondary GWs or even both these waves can possibly propagate further up to the thermosphere. These authors also pointed out that lower atmospheric GWs with convective sources penetrate into the thermosphere as higher order GWs.…”
Section: Discussionmentioning
confidence: 99%